Interventional Procedures Under the Guidance of Mammography in Breast Diseases - Fatma Nur Soylu Boy (Boğaziçi Tıp Dergisi, 2023)
Prompt and accurate histopathologic evaluation of breast lesions which are suspicious for malignancy is very important for early diagnosis and survival of breast cancer. Microcalcifications which are a sign of early breast cancer can be detected only by mammography. Biopsy and pre-operative localization of microcalcifications are only made by mammography guidance. At present, the standard procedure for mammographic biopsy is vacuum-assisted biopsy (VAB). VAB mostly provides accurate diagnosis without needing a surgery. This reduces the burden for the patients, clinicians, and the health system related with surgery. This review discusses the technical details and general evaluation of interventional procedures which are made by mammography guidance.